Meningkatkan Kemampuan Siswa dalam Menjumlahkan dan Mengurangkan Suatu Bilangan dengan Bantuan Media Batu Kerikil di Kelas I SDN 177/I Tapah Sari - Rusmini Rusmini (Jurnal Gentala Pendidikan Dasar, 2019)
The purpose of this study is to improve students' ability to add and subtract a number with the help of gravel media in class I students at SDN 177 / I Tapah Sari, Batanghari Regency, Jambi. This research was conducted in grade 1 students with a total of 13 male students and 11 female students. Before the improvement was held there were only 14 students who had not been able to reach the KKM 65, in the first cycle students who achieved KKM became 20 students, and in the second cycle increased to 24 students or all students had reached the KKM. From this study it can be seen that there is an increase in students' abilities as follows: On average before the holding of the improvement, 58.33% of the first cycle increased to 83.33% and in the second cycle increased again to 100%. This proves that the use of gravel media assistance can improve students' ability to add and subtract numbers.